An introduction to the field of commercializing emerging materials manufacturing technologies in an IoT world. (8th June 2018) - Tolfree, David; Walsh, Steven T
Abstract: Many see additive manufacturing (AM) and the internet of things (IoT) as two of the harbingers of the next Schumpeterian Cycle or Industry 4.0 (I 4.0). We use business cycle theory to demonstrate the technology basis for these technologies commercial interactions. We describe how AM techniques are poised to assist in overcoming hurdles in the IoT infrastructure technologies and how the IoT technologies are assisting AM based techniques. We discuss a model for AM application, and how international collaboration is speeding their co-development. We set the bases for the importance of emerging techniques in AM and the IoT that which are now helping to form the basis of I 4.0.